Reporting of adverse events following immunizations in Ghana – Using disproportionality analysis reporting ratios - Ankrah, Daniel N. A. (Hum Vaccin Immunother, 2017)
Background: Timely reporting of safety information post vaccination is pivotal for the success of any vaccination program. Reports of adverse events following immunization (AEFI) of 6 different vaccinations from Ghana were analysed for signals. Methods: De-identified data from active surveillance for AEFIs after 2009 AH1N1 influenza, yellow fever, meningitis, measles-rubella, pneumococcal-rotavirus and human papilloma virus vaccinations were used. All vaccinations occurred between January 2010 and December 2013. The ten most occurring events for each vaccination were captured and arranged using Medical Dictionary for Regulatory Authorities (MedDRA) Preferred Term (PT) and System Organ Classification (SOC) codes. Adverse event incidence rates were calculated for each vaccine type, and signals were generated using proportional reporting ratios (PRR). Results: A total number of 5,141 reports were analysed ranging from 33 (human papilloma virus) to 1958 (measles-rubella). Between 22% and 55% of all AEFIs per vaccine type were collected on the day of vaccination. For each vaccine type, at least 87% of all reported AEFIs occurred in the first 7 days post-vaccination. Multiple reports were received per vaccine type. For the MR vaccine, urticarial recorded the highest attack rate of 6.6 (95% CI 6.2, 7.1) per 100,000 vaccines. The AEFI with the highest PRR for both human papilloma and measles-rubella vaccines was abdominal pain, recording a PRR of 8.15 (95% CI 3.46, 19.23) and 43.75 (95% CI 17.81, 107.45) respectively. Conclusion: These results underscore the competency of public health systems in sub-Saharan African countries (like Ghana) to identify most frequently occurring and important vaccine related safety issues.